Advantages and Disadvantages of Diesel Single and Dual-Fuel Engines - Alberto Boretti; Alberto Boretti (Frontiers in Mechanical Engineering, 2019)
The pros and the cons of lean-burn, compression ignition (CI), direct injection (DI) internal combustion engines (ICE) are reviewed for transport applications. Fueling options considered include diesel only and dual-fuel applications with diesel and a gaseous fuel (CNG, LNG, and LPG). CIDI ICEs have higher fuel conversion efficiencies than stoichiometric, spark ignition (SI) ICEs, whether DI or port fuel injected (PFI). However, diesel-fueled CIDI ICEs have higher particulate matter (PM) and NOx engine-out emissions. The tail-pipe NOx emissions in real-world driving of diesel-powered vehicles have been, in the past, above the limits requested over the simplified cold start driving cycles used for certification. This issue has recently been resolved. The newest diesel-powered vehicles are now compliant with new laboratory test cycles and real-world-driving schedules and have no disadvantages in terms of criteria air pollutants compared to older diesel vehicles, while delivering improvements in fuel economy and CO2 emissions. Dual-fuel CIDI ICEs offer the opportunity for enhanced environmental friendliness. Dual-fuel CIDI ICEs have lower engine-out NOx and PM emissions compared to diesel-only CIDI ICEs. The latest diesel-only vehicles and vehicles with dual-fuel ICEs deliver dramatic reductions in tail-pipe PM emissions compared to older diesel-only vehicles. Moreover, they deliver tail-pipe PM emissions well below the ambient conditions in most city areas that are highly polluted, thereby helping to clean the air. The diesel-fueled CIDI ICEs may be further improved to deliver better fuel economy and further reduced tail-pipe emissions. The dual-fuel CIDI ICE has more room for improvement to produce similar or better steady state and transient performance in terms of torque, power output and fuel conversion efficiency compared to diesel-fueled CIDI ICEs, while drastically reducing CO2 and PM tail-pipe emissions, and improving NOx tail-pipe emissions. This is due to the ability to modulate the premixed and diffusion phases of combustion with a second fuel that is much easier to vaporize and is less prone to auto-ignition. Further development of the fuel injection system for the second fuel will lead to novel dual-fuel CIDI ICE designs with better performance.